2022
DOI: 10.3390/f13020211
|View full text |Cite
|
Sign up to set email alerts
|

Role of Egg Parasitoids in Controlling the Pine Processionary Moth in the Cedar Forests of Chréa National Park (Algeria)

Abstract: The sustainable protection of cedar stands in Chréa National Park can only be accomplished through the stability of the ecosystem. Outbreaks of Thaumetopoea pityocampa are a major threat and are largely attributed to the high population fecundity, changes in the diversity of natural enemies and global interactions within the ecosystem. Egg parasitoids (Hymenoptera) are essential in the biological control of T. pityocampa. To assess the impact of the parasitoids on the populations of the pine processionary moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…PPM occurrence rates are much lower in recent years than in previous seasons. These changes can be attributed mediated by global climate warming and repeated continuous insect control operations (Feracini et al, 2020;Sebti & Chakali, 2022). According to Ziouche et al, (2017), the insect is present in all bioclimatic stages, from the coast to the Saharan Atlas, and finds its optimal growth mainly in semi-arid and sub-humid areas.…”
Section: Discussionmentioning
confidence: 99%
“…PPM occurrence rates are much lower in recent years than in previous seasons. These changes can be attributed mediated by global climate warming and repeated continuous insect control operations (Feracini et al, 2020;Sebti & Chakali, 2022). According to Ziouche et al, (2017), the insect is present in all bioclimatic stages, from the coast to the Saharan Atlas, and finds its optimal growth mainly in semi-arid and sub-humid areas.…”
Section: Discussionmentioning
confidence: 99%
“…In the Chréa National Park in Algeria T. embryophagum parasitised between 1.95 and 8.81% of the eggs of pine processionary moth during the period 2010-2014 (Sebti et al, 2022). Two more species of egg parasitoids (O. pityocampae and B. servadeii) were found in cedar plantations in Algeria, but T. embryophagum dominated (Ayache et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that the natural enemies (e.g., parasitoids, predators, fungi, etc.) can play a significant role in the natural regulation of T. pityocampa and contribute to maintain their populations at low abundance levels within its distribution range (Tarasco et al 2016;Zamoum et al 2017;Rahim and Chakali 2022;Sebti et al 2022;Hein et al 2023;Lagogiannis et al 2023). Pimentel et al (2017) showed that the population density of T. pityocampa decreases dramatically after a year of severe defoliation as a consequence of both activity of the natural enemies and change in food quality (Pimentel et al 2017;Rahim et al 2021;Sebti et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The PPM has a univoltine lifecycle. In Algeria, the adults emerge, mate and lay eggs in a single clutch on pine needles or the underside of cedar twigs in July at colder sites and in August at warmer sites (Hezil et al 2018;Sebti et al 2022). Each egg batch contains, on average, in the northern regions of Algeria 220 eggs covered with protective scales, which are produced by the female .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation